Hypothesis Versus Fact: August Petermann and Polar Research - Tammiksaar, E.; Sukhova, N.G.; Stone, I.R. (ARCTIC, 1999)
The history of polar exploration has witnessed several conceptions of the climate, presence of lands, conditions of ice, and currents in the Arctic Ocean that were hypothetical or based on scarce research data. One such conception was the view of the physical geography of polar areas put forward in 1865 by the German geographer and publicist August Petermann, which was based mainly on the findings of English and Russian polar explorers. Although the actual course of polar research disproved Petermann's hypotheses, his conception not only exerted considerable influence on the development of the theoretical knowledge of polar areas, but also promoted practical steps in Arctic exploration during the second half of the 19th century. L'histoire de l'exploration polaire a été témoin de conceptions variées du climat, de la présence de terres, de conditions de la glace, et de courants dans l'océan Arctique, conceptions fondées sur des hypothèses ou de rares données de recherches. Une de ces conceptions, remontant à 1865, concernait la géographie physique des régions polaires telle que la voyait le géographe et publiciste allemand August Petermann, qui s'appuyait surtout sur les travaux d'explorateurs polaires anglais et russes. Bien que le cours récent de la recherche polaire réfute les hypothèses de Petermann, non seulement sa conception exerça une influence considérable sur le développement des connaissances théoriques des régions polaires, mais elle pava aussi la voie à des étapes pratiques dans l'exploration arctique durant la deuxième moitié du XIXe siècle.